Trabalho docente na rede pública de Uberlândia na conjuntura da indústria 4.0 e educação 4.0, no período de 2020 a 2023 - Castilho, Andressa Garcia (2024)
This doctoral thesis is authorized by Ethics and Research Committee in University of Uberlândia (UFU), and is included in the research line: Work, Society and Education, of the Postgraduate Program in Education of the University of Uberlândia (PPGED/UFU). The thesis aims to investigate how the processes of productive restructuring of capital in the context of Industry 4.0 and Education 4.0, impacted the teaching work in the municipal and state public schools of Uberlandia. From this, we cut the period from 2018 to 2022 in Brazil, for analysis on the conditions of teaching work. Regarding secondary objectives, they consist of: (a) describing the specificities and nature of the teaching work; (b) characterizing Industry 4.0 and Education 4.0; and (c) analyzing the teacher work of the public schools of Uberlandia, in the context of the Industrial Revolution and the Education 4.0. In this conjecture the theoretical-methodological propositions are set in the assumptions of dialectical historical materialism. In the year 2022, ten interviews were done, through the narratives of Oral History, with teachers in public institutions of Uberlândia, region of the Mineiro Triangle, in Minas Gerais State. For analysis of the sources obtained we use the categories: teaching work, class struggles, contradiction and hegemony. With this, through the studies of the Grupo de Pesquisa Experiências e Processos Sociais (GPEPS), and supported by the reports plus the theoretical contribution of: Antunes (2020-2023); Braverman (1977); Curry (1985); Freitas (2019), Fagiani (2022); Frigotto (2003); Hypolito (2023), Lombardi (2011); Mézarós (2008); Pistrak (2000); Previtali (202); Raimann (2015); Sanfelice (2007); Saviani (2008-2013); Shiroma (2020) and Edward Thompson (1992); analyses were performed. By obtaining results we can highlight it is possible to understand how Industry 4.0 emerges with new elements that were introduced in the educational models 4.0. It was up to the teachers to promote teaching based on new technologies and active methodologies. However, the conditions for this implementation hardly match the school reality. So education 4.0 and industry. 4.0 are within historical determinations, but are not consolidated in the practices and schools investigated, they present themselves more oriented to exploitation by extension of work and by low wages.